PROMOTIONAL STRATEGY ANALYSIS OF PT BNI SYARIAH MATARAM BRANCH IN ATTRACTING THE INTEREST OF IB HASANAH SAVINGS CUSTOMERS - Erly Janwariyana; Muh. Azkar (Jurnal Ekonomi, 2023)
This research aims to find out how the promotion strategy of PT BNI Syariah Mataram Branch is to attract the interest of iB Hasanah Savings customers. PT BNI Syariah Mataram Branch is a sharia-based financial institution. In promoting its products, especially iB Hasanah Savings products. Companies operating in the service sector, such as Bank BNI Syariah Mataram Branch, use four types of promotional tools, namely: Advertising, Sales Promotion, Personal Selling, and Publicity. This research is qualitative research that is descriptive qualitative in nature, trying to describe the research results obtained in the field. The type of data used in this research is primary and secondary data with the data sources used consisting of, Customer Service (CS), Fund Collection Sales, iB Hasanah Savings Customers, with data collection techniques used by researchers in the form of Non-Participant Observation, Interviews structured, and Documentation. The data obtained is then processed in the form of words which are then expressed in the form of a description or narrative. The results of this research are that the promotional strategy used by PT BNI Syariah Mataram Branch to Attract the Interest of iB Hasanah Savings Customers consists of four promotional tools, namely; Advertising (Advertising), Sales Promotion (Sales Promotion), Personal Selling (Personal Selling), and publicity (Publicity). This promotional strategy gives strength to Bank BNI Syariah Mataram Branch to compete with other banks.